2020
DOI: 10.1155/2020/4787202
|View full text |Cite
|
Sign up to set email alerts
|

PARK7 Diminishes Oxidative Stress-Induced Mucosal Damage in Celiac Disease

Abstract: Coeliac disease (CD) is a chronic, immune-mediated small intestinal enteropathy, accompanied with gluten-triggered oxidative damage of duodenal mucosa. Previously, our research group reported an increased mucosal level of the antioxidant protein Parkinson’s disease 7 (PARK7) in children with CD. In the present study, we investigated the role of increased PARK7 level on the epithelial cell and mucosal integrity of the small intestine. The presence of PARK7 was investigated using immunofluorescent staining on du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 42 publications
(46 reference statements)
1
12
0
Order By: Relevance
“…6 ) . In line with our previous experiments on small intestinal sacs 13 , we found that Comp23 greatly decreased the permeability of H 2 O 2 -treated colon sacs (Fig. 6 ), confirming the determinative role of PARK7 in the maintenance of mucosal integrity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…6 ) . In line with our previous experiments on small intestinal sacs 13 , we found that Comp23 greatly decreased the permeability of H 2 O 2 -treated colon sacs (Fig. 6 ), confirming the determinative role of PARK7 in the maintenance of mucosal integrity.…”
Section: Discussionsupporting
confidence: 92%
“…However, there are a few studies investigating the role of PARK7 in gastrointestinal diseases. Indeed, recently our research group demonstrated the role of PARK7 in the maintenance of duodenal mucosal integrity of children with coeliac disease 12 , 13 , and Di Narzo 23 and Zhang et al 24 investigated the amount of PARK7 in the plasma and intestine of adult patients with IBD, respectively. PARK7 was also shown to play a role in the pathomechanism of premature piglet model of enteral feeding induced necrotizing enterocolitis 25 , and in ketoprofen-induced oxidative damage of intestinal mucosa 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the proteins represented as increased in abundance in PS cows at 21 days BEC in Table 2, PARK7 and PRDX6 were both elevated. These proteins function as antioxidants that prevent buildup of oxidative species [24]. PS cows also exhibited an increased abundance of HSP70 at 21 days PP.…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA expressions were determined by real-time PCR using Light-Cycler 480 SYBR Green I Master enzyme mix on a LightCycler 96 system (Roche Diagnostics, Indianapolis, IN, USA). PCR primers (Table 2) were designed as previously described [51,52] and synthetized by Integrated DNA Technologies (IDT, Coralville, IA, USA). Results were analyzed using LightCycler 96 software v1.1.0.1320 (Roche Diagnostics).…”
Section: Rna Isolation and Cdna Synthesismentioning
confidence: 99%